Study of floating bodies in wave ny using smoothed particle hydrodynamics (SPH) [electronic resource] - Ha, Cheun Yuen, 1987- (2013)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2013